BIO -SYNTHEIS OF Fe2O3@SiO2@TiO2-Ag NANOCOMPOSITE USING ORANGE LEAVES EXTRACT AND ITS APPLICATION IN THE DEGRADATION OF METRONIDAZOLE USING SOLAR PHOTOCATALYTIC METHOD - F. A. Haider; A. I. Alwared (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
Sol-gel, co-precipitation, and photo-deposition techniques were combined to create an effective method for making Fe2O3@SiO2@TiO2-Ag nanoparticles magnetically separable photocatalyst. FTIR, SEM, EDS, and XRD techniques were used to characterize the Ag-doped composite using FTIR, SEM, EDS, and XRD. In addition, the prepared composites’ photocatalytic activity was investigated for the degradation of Metronidazole (MTZ). Approximately 96.85% of MTZ had decomposed after 2 hours of exposure to the sunlight with 20 mg/L of nanocomposite at a pH of 5, within 15 m/ L of MTZ. In addition, the outcomes showed that the 1-order kinetic model described the MTZ degradation kinetics. Furthermore, the results present that the Ag-doped composite was extremely efficient and reusable after 5 cycles of separation. Catching photo-generated electrons made charge separation easier by altering magnetic TiO2 with silver nanoparticles, which led to an increase in the enhanced photoactive ability. These results, demonstrating the fabrication Fe2O3@SiO2@TiO2-Ag nanoparticles, hold promising applications for the elimination of pharmaceutical residues in the presence of sun exposure.